An Endurance-Dominated Exercise Program Improves Maximum Oxygen Consumption, Ground Reaction Forces, and Muscle Activities in Patients With Moderate Diabetic Neuropathy - Jafarnezhadgero, AmirAli; Mamashli, Elahe; Granacher, Urs (Frontiers in Physiology, 2021)
Background: The prevalence of diabetes worldwide is predicted to increase from 2.8% in 2000 to 4.4% in 2030. Diabetic neuropathy is associated with damage to nerve glial cells, their axons, and endothelial cells leading to impaired function and mobility. Objective: We aimed to examine the effects of an endurance-dominated exercise program on maximum oxygen consumption(VO2max), ground reaction forces, and muscle activities during walking in patients with moderate diabetic neuropathy. Methods: Sixty male and female individuals aged 45-65 years with diabetic neuropathy were randomly assigned to an intervention (IG,n=30) or a waiting control (CON,n=30) group. The research protocol of this study was registered with the Local Clinical Trial Organization (IRCT20200201046326N1). IG conducted an endurance-dominated exercise program including exercises on a bike ergometer and gait therapy. The progressive intervention program lasted 12 weeks with 3 sessions per week, each 40-55 minutes. CON received the same treatment as IG after the post-tests. Pre and post training, VO2max was tested during a graded exercise test using spiroergometry. In addition, ground reaction forces and lower limbs muscle activities were recorded while walking at a constant speed of ⁓1 m/s. Results: Significant group-by-time interactions were found for VO2max (p<0.001;d=1.22). The post-hoc test revealed a significant increase in IG (p<0.001;d=1.88) but not CON. Significant group-by-time interactions were observed for peak lateral and vertical ground reaction forces during heel contact and peak vertical ground reaction force during push-off (p=0.001-0.037;d=0.56-1.53). For IG, post-hoc analyses showed decreases in peak lateral (p<0.001;d=1.33) and vertical (p=0.004;d=0.55) ground reaction forces during heel contact. In terms of muscle activity, significant group-by-time interactions were found for vastus lateralis and gluteus medius during the loading phase and for vastus medialis during the mid-stance phase, and gastrocnemius medialis during the push-off phase (p=0.001-0.044;d=0.54-0.81). Conclusions: This study demonstrated that an endurance-dominated exercise program has the potential to improve VO2max and diabetes-related abnormal gait in patients with diabetic neuropathy. Accordingly, we recommend to implement endurance-dominated exercise programs in type 2 diabetic patients because it is feasible, safe and effective by improving aerobic capacity and gait characteristics.